2016
DOI: 10.1111/1468-4446.12237
|View full text |Cite
|
Sign up to set email alerts
|

Continuity, change and complexity in the performance of masculinity among elite young footballers in England

Abstract: Following recent research evidencing that young men are redefining the essential components of what it is to be a man, this paper draws on qualitative interviews with 22 elite-level, English Premier League academy level football (soccer) players to investigate their performances and understandings of masculinity in relation to decreasing homohysteria. Even in this gender-segregated, near-total institution, these working-class, non-educationally aspiring adolescents evidence an attenuated performance of 'malene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…Even so, though, he still said that, "It depends on who it is…I don't actively try to avoid touching them, I just don't feel the need to." Given that alcohol has been shown to have a profound effect on the expression of contemporary masculinities (Anderson et al, 2012;Roberts, Anderson and Magrath, in press), it is unsurprising that this also emerged as a significant factor for men in this studyand their elevation of physical affection. Evidencing this, Lewis said that, "On nights out there was a lot of hugging and cuddling.…”
Section: Fondly Recalling University Friendshipmentioning
confidence: 77%
“…Even so, though, he still said that, "It depends on who it is…I don't actively try to avoid touching them, I just don't feel the need to." Given that alcohol has been shown to have a profound effect on the expression of contemporary masculinities (Anderson et al, 2012;Roberts, Anderson and Magrath, in press), it is unsurprising that this also emerged as a significant factor for men in this studyand their elevation of physical affection. Evidencing this, Lewis said that, "On nights out there was a lot of hugging and cuddling.…”
Section: Fondly Recalling University Friendshipmentioning
confidence: 77%
“…The purpose of this research was to examine the contextually relevant experiences of the first-ever openly gay elite athlete in a Spanish team sport. This research therefore drew on existing literature on gay men in sport, while also providing one of the few examinations of this topic outside of the USA (Cleland, 2014a, 2014b; Roberts et al, 2017). It enhances the existing sociological literature because it addresses a gap in research concerning the experiences of openly gay elite athletes, especially in the Spanish context.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular note, a British study of heterosexual male students aged sixteen to twenty-five by Anderson, Adams, and Rivers (2012), and an Australian study of male undergraduate students by Drummond et al (2015), found significant proportions of participants had engaged in various types of same-sex kissing. Similarly, McCormack’s (2012, 2014) ethnographic study of homophobia in British high schools; Robinson, Anderson, and White’s (2018) study of bromance; Roberts, Anderson, and Magrath’s (2017) study of elite football players; and Scoats’s (2015) analysis of Facebook images also reported increasing physical intimacy between young men from a variety of social backgrounds and in heterogeneous contexts. Each study identifies men’s increasing acceptance of homosexuality and a resulting shift in the physical and emotional boundaries of heteromasculinity (Anderson 2009).…”
Section: Imt and A Disintegrating Masculine Hierarchymentioning
confidence: 94%